2009
DOI: 10.1016/j.dental.2009.06.014
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the elastic/plastic transition of human enamel by nanoindentation

Abstract: We believe these data are also a valuable contribution to understand the mechanical behavior of enamel and to develop nanoscale biomimetic materials.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(29 citation statements)
references
References 34 publications
1
28
0
Order By: Relevance
“…2g and h. The deformation behaviour of the enamel from all three regions was rather linear before fracture, suggesting little plasticity up to the point of fracture. Ang et al 9 reported plastic deformation in enamel during nanoindentation, but the stress state in the indentation situation is mainly compressive and shear, and this may help suppress fracture and enable plasticity to occur. In a bend test, the upper portion of the specimen is under tension which favors crack propagation, and so it is not surprising to have little plasticity prior to fracture.…”
Section: Discussionmentioning
confidence: 98%
“…2g and h. The deformation behaviour of the enamel from all three regions was rather linear before fracture, suggesting little plasticity up to the point of fracture. Ang et al 9 reported plastic deformation in enamel during nanoindentation, but the stress state in the indentation situation is mainly compressive and shear, and this may help suppress fracture and enable plasticity to occur. In a bend test, the upper portion of the specimen is under tension which favors crack propagation, and so it is not surprising to have little plasticity prior to fracture.…”
Section: Discussionmentioning
confidence: 98%
“…where ] is Poisson's ratio (∼0.28) of enamel nanocomposite [33] and the other terms are already explained. Thus, the work of fracture ( ) was estimated to be ∼7 J⋅m −2 which was of the order of data (∼13 J⋅m −2 ) reported in the literature [49], thereby suggesting that the average experimental value of 0.88 MPa⋅m 0.5 for IC(e) of the enamel nanocomposite was reasonable.…”
Section: Discussionmentioning
confidence: 99%
“…It was shown further that prevention of cracks formed in enamel nanocomposite from traversing the interface and causing catastrophic tooth fractures was not necessarily associated with the crack-arrest capabilities of the DEJ itself but rather with the development of crack-tip shielding, primarily from uncracked-ligament bridging, in the mantle dentin region adjacent to the DEJ [39]. DEJ zone thus plays a crucial role for the structural stability of teeth, but the details of how this zone acts as a crack-arrest barrier for flaws formed in the brittle enamel nanocomposite have not been understood fully [22,23,26,28,29,32,33,36].…”
Section: Introductionmentioning
confidence: 99%
“…During investigation of submicrocrystalline ceramics intra-grain structure of nanocrystalline and microcrystalline HA coatings with equilibrium grain structure [2][3][4][5][6][7][8][9] and of the coatings regions upon nanoindentation [2] growth-induced and strain-induced dislocations in the grains bulk have not been found. Frank dislocations, related to stacking faults in indentation deformed regions of fluorine-substituted HA single crystal have been revealed [1].…”
Section: Introductionmentioning
confidence: 99%
“…It is known that deformations of microcrystals [3], HA ceramics [4], human dental enamel [5] and HA-based coatings of different structures [6][7][8] are elastic-plastic. In Ref.…”
Section: Introductionmentioning
confidence: 99%